Design of Blade of Mixed Flow Pump Impeller Using Mean Stream Line Method. (2016) - Zindani, Divya; Roy, Apurba Kumar; Kumar, Kaushik
Abstract: Designing of mixed flow impeller blades is still a cumbersome task, mainly due to the great number of geometric parameters. From the day of its invention various methods have been used for designing the same. Some of the prominent methods are inverse time marching method, the pseudo-stream function method, Fourier expansion singularity method, free vortex method, mean stream line theory method etc. All of these have their own merits and demerits. In this work mean stream line theory has been used for the designing of blades. It has been observed that this method, although used sparingly, gave results comparable to the other methods.